Comparative performance data for multiplex SARS-CoV-2 serological assays from a large panel of dried blood spot specimens. Issue 9 (September 2022) - Cholette, François; Fabia, Rissa; Harris, Angela; Ellis, Hannah; Cachero, Karla; Schroeder, Lukas; Mesa, Christine; Lacap, Philip; Arnold, Corey; Galipeau, Yannick; Langlois, Marc-André; Colwill, Karen; et al.
Abstract: The extent of the COVID-19 pandemic will be better understood through serosurveys and SARS-CoV-2 antibody testing. Dried blood spot (DBS) samples will play a central role in large scale serosurveillance by simplifying biological specimen collection and transportation, especially in Canada. Direct comparative performance data on multiplex SARS-CoV-2 assays resulting from identical DBS samples are currently lacking. In our study, we aimed to provide performance data for the BioPlex 2200 SARS-CoV-2 IgG (Bio-Rad), V-PLEX SARS-CoV-2 Panel 2 IgG (MSD), and Elecsys Anti-SARS-CoV-2 (Roche) commercial assays, as well as for two highly scalable in-house assays (University of Ottawa and Mount Sinai Hospital protocols) to assess their suitability for DBS-based SARS-CoV-2 DBS serosurveillance. These assays were evaluated against identical panels of DBS samples collected from convalescent COVID-19 patients ( n = 97) and individuals undergoing routine sexually transmitted and bloodborne infection (STBBI) testing prior to the COVID-19 pandemic ( n = 90). Our findings suggest that several assays are suitable for serosurveillance (sensitivity >97% and specificity >98%). In contrast to other reports, we did not observe an improvement in performance using multiple antigen consensus-based rules to establish overall seropositivity. This may be due to our DBS panel which consisted of samples collected from convalescent COVID-19 patients with significant anti-spike, -receptor binding domain (RBD), and -nucleocapsid antibody titers. This study demonstrates that biological specimens collected as DBS coupled with one of several readily available assays are useful for large-scale COVID-19 serosurveillance. Abstract : SARS-CoV-2; covid-19; Dried Blood Spots; Serology; immunoassays; serosurveys.